If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -20 + -10x = 8x + -16 Reorder the terms: -20 + -10x = -16 + 8x Solving -20 + -10x = -16 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -20 + -10x + -8x = -16 + 8x + -8x Combine like terms: -10x + -8x = -18x -20 + -18x = -16 + 8x + -8x Combine like terms: 8x + -8x = 0 -20 + -18x = -16 + 0 -20 + -18x = -16 Add '20' to each side of the equation. -20 + 20 + -18x = -16 + 20 Combine like terms: -20 + 20 = 0 0 + -18x = -16 + 20 -18x = -16 + 20 Combine like terms: -16 + 20 = 4 -18x = 4 Divide each side by '-18'. x = -0.2222222222 Simplifying x = -0.2222222222
| x(x)=999999999999999999999999999999999999 | | x(x)=1111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111111 | | x(x)=-1 | | x(x)=2 | | x(x)+9999999x+10000000=0 | | 20-3x=8-7x | | x(x)(x)+3x(x)+3x+1=0 | | x(x)(y)(y)+4xy+3=0 | | y-4=4(x+3) | | 67-6x=9+22 | | x(y)+4xy+3=0 | | x(x)+4x+3=0 | | 2x+13=76+5x | | x+y=x(x) | | x+x=x+x | | (x)(y)(x+1)(y+1)=1 | | (x)(x)(x)(x)(x)(x)(x)(x)(x)(x)(x)(x)(x)=1 | | x(x)(x)=1 | | 2t^2+21t+52=0 | | 15-2(x+3)=x+9 | | 7(x+7)=2x-1 | | 29+x=7x+5 | | 13-(-2x+5)=8 | | 6+10=416 | | 4t^3-4t=0 | | x(x-28)=-196 | | y=-1/2x+8 | | 4x+13=57 | | 7ln(4x)=28 | | 8y-28=3y+2 | | -1/2x+8=1x+2 | | x-3=x^2 |